Interrelation of indicators of body composition with the effectiveness of competitive activity of highly qualified biathletes - Zagursky, N. S.; Romanova, Ya. S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the relationship between the body composition of highly qualified biathletes and the indicators of competitive activity at the stages of long-term training.